איך אתה לפשט (4 + sqrt50) - (3-sqrt (8))?

איך אתה לפשט (4 + sqrt50) - (3-sqrt (8))?
Anonim

תשובה:

# = 1 + 7sqrt2 #

הסבר:

# sqrt50 = 5sqrt2 # ו # sqrt8 = 2sqrt2 #

משוואה הופכת # (4 + 5sqrt2) - (3-2sqrt2) #

# = 4 + 5sqrt2-3 + 2sqrt2 #

# = 1 + 7sqrt2 #

תשובה:

# (4 + sqrt50) - (3-sqrt8) = 1 + 7sqrt2 #

הסבר:

# (4 + sqrt50) - (3-sqrt8) # #

# sqrt50 = sqrt (25xx2) = sqrt25xxsqrt2 = 5sqrt2 #

# sqrt8 = sqrt (4xx2) = sqrt4xxsqrt2 = 2sqrt2 #

# (4 + sqrt50) - (3-sqrt8) = (4 + 5sqrt2) - (3-2sqrt2) #

# = 4 + 5sqrt2-3 + 2sqrt2 #

# = (4-3) + (5sqrt2 + 2sqrt2) #

# = 1 + 7sqrt2 #

# (4 + sqrt50) - (3-sqrt8) = 1 + 7sqrt2 #